PENGEMBANGAN INSTRUMEN TES ESAI BERBASIS KEMAMPUAN BERPIKIR KRITIS PADA MATERI GARIS DAN SUDUT DI TINGKAT SMP - Kusumo, Bangun Jati; Hepsi Nindiasari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Research and development (R&D) is the focus of this study. The purpose of this research is to develop an essay exam instrument for junior high school students based on critical thinking abilities about lines and angles. In this study,